Pollution Assessment of Surface and Drainage Water by Heavy Elements in Al Ahrar District, Wasit Governorate, Iraq - Al-Shamma'a, Ayser; Hassan, Reyam A. (Iraqi Journal of Science, 2018)
The study area lies in Wasit governorate south west Kut city, where Al Ahdeb oil field is located to the south of Al Ahrar district. The present study deals with assessment of heavy metals pollution in water by collecting eleven water samples (five samples from drainage and six samples from surface water) in 5th of December 2016. The water samples analysis of heavy elements in the study area shown that water is polluted with high concentration of (Pb, Cd) elements, while the concentration of (Cu, Fe, Zn) in water samples are within the permissible limits of both World Health Organization, and Iraqi standards and there are no hazard effects from these elements. The study detected some diseases that injured the people living in the vicinity of the oil field complex such as scabies, vitiligo, eczema and contact dermatitis, as a result of increasing of (Pb) ion in water samples.